Improving Convenience or Saving Face? An Empirical Analysis of the Use of Facial Recognition Payment Technology in Retail - Gao, Jia; Rong, Ying; Tian, Xin; Yao, Yuliang (Information Systems Research, 2024)
Facial recognition payment technology (FR) has the potential to disrupt the offline retailing industry by automating the payment process. However, some firms that adopted FR payment technology have experienced only moderate success, and many customers have expressed frustration using FR payment technology. By utilizing data sets from three retail chains, we find that customers are less likely to use FR payment technology during self-checkouts when more customers are in line behind them, waiting and watching (the social presence effect), and when more preceding customers use the other payment technology (the herding effect). These findings imply that (1) the design of FR technology can be improved to alleviate the social presence effect (such as adding a privacy screen filter or beautify the appearance of the consumer’s image), and (2) monetary incentives may be used to attract more users by leveraging the herding effect.